2018
DOI: 10.1063/1.5042013
|View full text |Cite
|
Sign up to set email alerts
|

Hot-carrier-mediated impact excitation of Er3+ ions in SiO2 sensitized by Si Nanocrystals

Abstract: Past research has shown that indirect excitation of Er 3þ ions in SiO 2 solid-state matrix with Si nanocrystals can be achieved by different pathways. Here, we investigate the impact excitation mechanisms in detail by means of time-resolved photoluminescence spectroscopy. We explicitly demonstrate that the free carrier impact excitation mechanism is activated as soon as the carriers obtain sufficient excess energy. The "hot" carriers with the above-threshold energy can be created upon optical pumping in two wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This Si NPs related PL is inhibited after 800°C annealing owing to Si combining with other elements to form zinc silicide [27]. Furthermore, when Si NPs grow to an appropriate size, the 1.16-μm emission is suppressed and energy transfer between Si NPs and Er 3+ ions occurs [28,29]. These observations are consistent with our earlier suggestions that the 1.54-μm PL depends on the size distribution of the formed Si-NPs, and on their coupling with Er ions.…”
Section: Resultsmentioning
confidence: 99%
“…This Si NPs related PL is inhibited after 800°C annealing owing to Si combining with other elements to form zinc silicide [27]. Furthermore, when Si NPs grow to an appropriate size, the 1.16-μm emission is suppressed and energy transfer between Si NPs and Er 3+ ions occurs [28,29]. These observations are consistent with our earlier suggestions that the 1.54-μm PL depends on the size distribution of the formed Si-NPs, and on their coupling with Er ions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the excitation of Er-doped insulating materials cannot be effective due to the small effective cross section for resonant excitation [9]. In recent years, the main approach to improve the efficiency of Er luminescence and avoid the need for high excitation powers has been to take advantage of energy transfer from silicon nanocrystals [8,[10][11][12][13]]. However, it has been shown that only ions in close proximity to Si-ncs can be excited and that the optically active concentration of rare earth ions remains very low [14].…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Benefitting from the shielding effect of the 4f shell in Er ions, a narrow emission band with a temperature invariant wavelength can be obtained up to room temperature. 5) Wu et al have investigated the structural and optical characteristics of Er-doped GaN powder and observed a green emission. 6) Birkhahn and Steckl have observed green emission at 537 and 558 nm from Er-doped GaN films grown on Si.…”
Section: Introductionmentioning
confidence: 99%